2017
DOI: 10.1002/14651858.cd011899.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based versus in-person interventions for preventing and reducing stress in workers

Abstract: We found very low-quality evidence with conflicting results, when comparing the effectiveness of computer-based stress management interventions with in-person stress management interventions in employees. We could include only two studies with small sample sizes. We have very little confidence in the effect estimates. It is very likely that future studies will change these conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 119 publications
1
14
0
Order By: Relevance
“…Approximately one-third of the articles for some outcomes (eg, insomnia and burnout) were written by the same investigation team, which may cause author bias. High dropout rates (>20%) are another common problem of e-health intervention studies, and this was reinforced by the present review; more than half of the studies (25) suffered from high attrition rates, while five studies did not report on attrition. Thus, it was impossible to appraise the bias associated with missing outcome data.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Approximately one-third of the articles for some outcomes (eg, insomnia and burnout) were written by the same investigation team, which may cause author bias. High dropout rates (>20%) are another common problem of e-health intervention studies, and this was reinforced by the present review; more than half of the studies (25) suffered from high attrition rates, while five studies did not report on attrition. Thus, it was impossible to appraise the bias associated with missing outcome data.…”
Section: Discussionsupporting
confidence: 59%
“…The evidence regarding occupational e-mental health is more limited. Kuster et al (25) reviewed two studies with computer-based versus in-person stress management programs. The results of the review were conflicting, and the authors considered the studies to offer low-quality evidence.…”
mentioning
confidence: 99%
“…Out of the 16 Cochrane reviews identified, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] eight were targeted at general health, physical health or lifestyle behaviour. This included reviews related to improving physical activity through the use of pedometers, 37 decreasing sitting time at work, 46 sex risk behaviour and preventing human immunodeficiency virus (HIV) infection, 43 and smoking cessation.…”
Section: Cochrane Reviewsmentioning
confidence: 99%
“…In a meta-analysis, Andersson et al (20) reported equal treatment success following face-to-face versus internet based psychological treatments in conjunction with various mental disorders. Nevertheless, a direct comparison of stress management training interventions that solely differ in a computer based and a person-centered presentation revealed no clear results (21)(22)(23).…”
Section: Introductionmentioning
confidence: 96%